Molecular Identification of Invasive Non-typeable Group B Streptococcus Isolates From Denmark (2015 to 2017) - Slotved, Hans-Christian; Fuursted, Kurt; Kavalari, Ioanna Drakaki; Hoffmann, Steen (Frontiers in Cellular and Infection Microbiology, 2021)
The number of invasive Streptococcus agalactiae (GBS) non-typeable (NT) isolates in Denmark received since 1999 has in general accounted for 10% of all invasive GBS isolates. We present data on 55 clinical NT isolates based on clinical manifestations, clonal relationship, antimicrobial resistance (AMR) determinants and virulence factors. The GBS isolates included in this study were phenotypic-based NT obtained from 2015 – 2017, as well as ten reference isolates. Whole genome sequencing (WGS) was performed on all isolates and the data were analysed for the presence of both species specific genes, capsular genes (genotype), and other relevant genes. We furthermore compared different procedures for detection of serotype specific capsular genes. Overall we were able to genotype 54 of the 55 isolates. After retesting the isolates a phenotype was detected for 20 (36 %) isolates, of which the initial phenotyping problem for 13 isolates was found to be due to a problem with serotype Ia specific antiserum. 35 isolates remained phenotypic non-typeable with a majority of genotype V isolates which do not express a capsular gene. From all the Danish invasive GBS isolates from 2015 – 2017, was the 35 NT isolates only detected in the age group above 21 years with bacteremia. The 35 NT isolates belonged to 6 different well-known human pathogenic clonal complexes. The CDC recommended sequences for capsule genotyping were the most optimal for serotype prediction, because of the sequence simplicity and clear cutoff values. However we recommend to also use other capsular sequences for the NT isolates, if they cannot be genotyped by the CDC method.